2022
DOI: 10.1007/s12144-022-03270-0
|View full text |Cite
|
Sign up to set email alerts
|

Deviant peer affiliation as a mediating variable in the relationship between family cohesion and adaptability and internet addiction among adolescents

Abstract: The aim of this study was to investigate the mediating role of deviant peer affiliation in the relationship between family functioning, specifically family cohesion and family adaptability, and internet addiction among Saudi adolescents. A sample of 946 Saudi Arabian adolescents with a mean age of 18.5 years (SD = 3.06) was obtained using snowball sampling. Path analysis using structural equation modeling was conducted. The results indicated significant negative relationships between family cohesion and intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Particularly, peer affiliation has a strong influence on university students 72 , 73 and is a protective factor against smartphone addiction, 18 whereas deviant peer affiliation exacerbates addictive behaviors. 74 …”
Section: Discussionmentioning
confidence: 99%
“…Particularly, peer affiliation has a strong influence on university students 72 , 73 and is a protective factor against smartphone addiction, 18 whereas deviant peer affiliation exacerbates addictive behaviors. 74 …”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous studies which have shown a positive correlation between terrible family environment and addictive behavior in teenagers (Ko et al, 2007 ; Salimi et al, 2016 ; Chung et al, 2019 ). Adolescents who experience lower family cohesion may be more likely to seek out external attention, including through mobile phones via the Internet (Sarour and El Keshky, 2022 ), as a means of emotional regulation (Park et al, 2008 ), which could lead to over-dependence on mobile phones.…”
Section: Discussionmentioning
confidence: 99%
“…behavior in teenagers (Ko et al, 2007;Salimi et al, 2016;Chung et al, 2019). Adolescents who experience lower family cohesion may be more likely to seek out external attention, including through mobile phones via the Internet (Sarour and El Keshky, 2022), as a means of emotional regulation (Park et al, 2008), which could lead to over-dependence on mobile phones. Compared to the mediating factor assumed in the prior studies (Niu et al, 2020;Zhang et al, 2021;Wang et al, 2022;Wei et al, 2022a), the mediation of parent-child cohesion underlines the important role of environmental variable instead of personal variable.…”
Section: Figurementioning
confidence: 99%
“…Nevertheless, this does not signify that family has less of an influence on adolescent development [2,19]. In fact, the effects of family socialization are persistent and steadfast, meaning that instead of exerting direct impacts on child development, families may influence their adolescent children indirectly by swaying their methods of interacting with their schools and peer systems [16,46,47]. Thus, as is consistent with the person-in-environment perspective and social systems theory [3,4], human service and public health practitioners should take note of the dynamic and conditional effects of different contextual systems on female adolescent development [2,5,48,49].…”
Section: Discussionmentioning
confidence: 99%